2007
DOI: 10.1016/j.pain.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Nerve injury-induced tactile allodynia is present in the absence of FOS labeling in retrogradely labeled post-synaptic dorsal column neurons

Abstract: The dorsal column pathway consists of direct projections from primary afferents and of ascending fibers of the post-synaptic dorsal column (PSDC) cells. This pathway mediates touch but may also mediate allodynia after nerve injury. The role of PSDC neurons in nerve injury-induced mechanical allodynia is unknown. Repetitive gentle, tactile stimulus or noxious pinch was applied to the ipsilateral hindpaw of rats with spinal nerve ligation (SNL) or sham surgery that had previously received tetramethylrhodamine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…The SNT model is a validated and common model to study mechanisms underlying neuropathy-induced pain sensitivity. In line with previous work by Zhang and colleagues, we found that stroking the hindpaw ipsilateral to spinal nerve injury resulted in an increased number of neurons expressing the early neuronal activation marker cFos (Zhang et al, 2007). This increase was observed in the superficial dorsal horn of the lumbar spinal cord.…”
Section: Spinal Gap-43 Expression and Nerve Injurysupporting
confidence: 92%
See 1 more Smart Citation
“…The SNT model is a validated and common model to study mechanisms underlying neuropathy-induced pain sensitivity. In line with previous work by Zhang and colleagues, we found that stroking the hindpaw ipsilateral to spinal nerve injury resulted in an increased number of neurons expressing the early neuronal activation marker cFos (Zhang et al, 2007). This increase was observed in the superficial dorsal horn of the lumbar spinal cord.…”
Section: Spinal Gap-43 Expression and Nerve Injurysupporting
confidence: 92%
“…Five days following SNT, another cohort of animals (n = 6) received non-nociceptive stimulation as previously described (Zhang et al, 2007). The animals were habituated to the experimenter.…”
Section: Non-nociceptive Stimulation Of L5 Snt Animalsmentioning
confidence: 99%
“…Previous studies have demonstrated that normally non-noxious stimulation, such as light touch, produces FOS expression within the spinal dorsal horn of rats with CFA induced inflammation 24 . FOS is an early oncogene that is selectively expressed in response to neuronal activation 24 , and is not normally observed in the spinal dorsal horn in the absence of noxious stimulation in the absence of injury 24, 34, 44 . Spinal FOS expression in response to normally non-noxious stimulation has been used to measure the development of injury-induced spinal sensitization across models of inflammation-, nerve-injury- and cancer-induced pain states 24, 34, 44 .…”
Section: Discussionmentioning
confidence: 99%
“…FOS is an early oncogene that is selectively expressed in response to neuronal activation 24 , and is not normally observed in the spinal dorsal horn in the absence of noxious stimulation in the absence of injury 24, 34, 44 . Spinal FOS expression in response to normally non-noxious stimulation has been used to measure the development of injury-induced spinal sensitization across models of inflammation-, nerve-injury- and cancer-induced pain states 24, 34, 44 . Our observations demonstrate that movement of the MIA treated knee joint selectively induces FOS expression in the spinal dorsal horn of high dose MIA treated rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation